Urban Lifestyle and Environmental Awareness as Predictors of Outdoor Apparel Consumption among Nature Lover Students - Didit Darmawan; Amelia Pristian Syah Putri (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to examine the effect of urban lifestyle and environmental awareness on outdoor apparel consumption among students who are members of the Nature Lovers Student Activity Unit in Surabaya, Malang, and Sidoarjo. A quantitative approach with an explanatory research method was used in this study. Data analysis was performed using multiple linear regression after fulfilling the classical assumption test. The results show that urban lifestyle has a positive and significant effect on outdoor apparel consumption. Environmental awareness also has a positive and significant effect on outdoor apparel consumption. Simultaneously, both independent variables have a significant effect. These findings reinforce the Theory of Planned Behavior, Value-Belief-Norm Theory, and Consumer Culture Theory in the context of outdoor apparel consumption among nature-loving students in urban areas.